Bandwidth Extension in Cascaded Single-Stage Distributed Microwave Amplifier - A. Ali, Ali; R. Kareem, Azad (Journal of Engineering and Sustainable Development, 2005)
In this paper the principles of wideband microwave amplifier will be highlighted. Special attention goes to the design methodology of high-gain cascaded single-stage distributed amplifiers (CSSDA). Alternation to the basic design including the use of “cascode” gain cells is then discussed. This is a new technique for enhancing the bandwidth of the amplifier. The final design is implemented using microwave office program. A four-stage CSSDA with and without cascode cells were tested in order to demonstrate the validity of the proposed method.